Use of perfusional CBCT imaging for intraprocedural evaluation of endovascular treatment in patients with diabetic foot: a concept paper - Gurgitano, Martina; Signorelli, Giulia; Rodà, Giovanni Maria; Liguori, Alessandro; Pandolfi, Marco; Granata, Giuseppe; Arrichiello, Antonio; Ierardi, Anna Maria; Paolucci, Aldo; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2020)
Diabetes mellitus (DM) is one of the most common metabolic diseases worldwide; its global burden has increased rapidly over the past decade, enough to be considered a public health emergency in many countries. Diabetic foot disease and, particularly diabetic foot ulceration, is the major complication of DM: through a skin damage of the foot, with a loss of epithelial tissue, it can deepen to muscles and bones and lead to the amputation of the lower limbs. Peripheral arterial disease (PAD) in patients with diabetes, manifests like a diffuse macroangiopathic multi-segmental involvement of the lower limb vessels, also connected to a damage of collateral circulation; it may also display characteristic microaneurysms and tortuosity in distal arteries. As validation method, Bold-MRI is used. The diabetic foot should be handled with a multidisciplinary team approach, as its management requires systemic and localized treatments, pain control, monitoring of cardiovascular risk factors and other comorbidities. CBCT is an emerging medical imaging technique with the original feature of divergent radiation, forming a cone, in contrast with the spiral slicing of conventional CT, and has become increasingly important in treatment planning and diagnosis: from small anatomical areas, such as implantology, to the world of interventional radiology, with a wide range of applications: as guidance for biopsies or ablation treatments. The aim of this project is to evaluate the usefulness of perfusion CBCT imaging, obtained during endovascular revascularization, for intraprocedural evaluation of endovascular treatment in patients with diabetic foot.